Edificando comunidades: a educação musical a serviço do reino de Deus - Gauger, Ernâni Luís (2011)
This work studies the Musical Education of children and young people as part of integration and engagement of them in community life and also as promoter of community edification. It is characterized as a study case from a qualitative descriptive study. From the reality of a communitarian Music Education, interviews were conducted with people involved in the project, in other words, some students, the teacher, the workers, presbyters and students relatives. The data collected were analyzed in order to identify the contributions to Musical Education in the community edification. To support and document the analysis the theoretical background was inquired, through bibliographic research, referring to the works of some theorists in the Education and Theology areas. The first chapter talks about the presence of Music in the Bible and makes a brief recovery of the historicity of Musical Education in the world, in Brazil, in the Evangelical Church of Lutheran Confession in Brazil, in the northwest region of Rio Grande do Sul state and in the community where the project was carried out. The second chapter presents some concepts of the expression: edify communities and then proceeds to analyze the results of the field research, comparing the statements of the interviewers with the consulted bibliography. The third chapter reveals some practical conclusions for the work of Music Education, because of its musical, personal and communitarian dimension. Finally, some actions for the organization and implementation of Music Education projects in IECLB communities and other religious denominations are suggested.